2015
DOI: 10.9710/kjm.2015.31.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distances of three venerid species identified by PCR analysis

Abstract: The seven selected primers and BION-80 generated the total number of loci, average number of loci per lane and specific loci in Meretrix lusoria (ML), Saxidomus purpuratus (SP) and Cyclina sinensis (CS) species. Here, the complexity of the banding patterns varied dramatically between the primers from the three venerid clam species. The higher fragment sizes (> 1,000 bp) are much more observed in the SP species. The primer BION-68 generated 21 unique loci to each species, which were ascertaining each species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…purpuratus species (0.607) (p<0.05) in the three venerid shellfish species (Jeon & Yoon, 2015). This author reported that complete linkage cluster method, which indicated binary genetic groupings, and the dendrogram revealed a close relationship between the identities within binary PSTs.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…purpuratus species (0.607) (p<0.05) in the three venerid shellfish species (Jeon & Yoon, 2015). This author reported that complete linkage cluster method, which indicated binary genetic groupings, and the dendrogram revealed a close relationship between the identities within binary PSTs.…”
Section: Resultsmentioning
confidence: 75%
“…Related discretely, the ABS grades of the entities PSTA were higher than those from PSTB. To discriminate, the ABS amounts of individuals in the Charybdis crab population A (CCPA) (0.575±0.014) were lesser than in those originated from the Charybdis crab population B (CCPB) (0.705±0.011) ( p <0.05) ( Yoon, 2022 ), and entities from Cyclina sinensis species (0.754) displayed higher BS amounts than did entities from Saxidomus purpuratus species (0.607) ( p <0.05) in the three venerid shellfish species ( Jeon & Yoon, 2015 ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation